A Review on the Physicochemical and Biological Aspects of the Chitosan Antifungal Activity in Agricultural Applications - Velásquez, Cristóbal Lárez; Avelizapa, Luz Rojas (Journal of Research Updates in Polymer Science, 2020)
The antifungal activity of the chitosan biopolymer has been extensively studied for several decades. However, the mechanisms of action associated with this process have not been fully clarified yet. To a large extent, this situation is due to the lack of systematization with which, in general terms, the subject has been approached. However, it seems to have begun to change in recent years with the appearance of several papers reviewing the accumulated knowledge on the beneficial effects shown by chitosan in agricultural applications and putting forward it in a more systematic mode. In this work, the most relevant mechanisms of action proposed for chitosan regarding its antifungal activity will be briefly presented, i.e., disruption and changes in the fungal plasma membrane, alteration of gene expression, inhibition of RNA and protein synthesis, Ca2+ channel blocker, to then address the main factors that influence this antifungal activity, observed mainly in studies focused on phytopathogenic species, which have been grouped into three main blocks: those related exclusively to the chitosan molecules, those associated to the fungal itself and those having to do with the environment where the processes take place. Additionally, a brief section addressing some possibilities on which future studies on this topic should focus is also included.